2021
DOI: 10.1097/sla.0000000000004984
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 Producing T Lymphocytes Attenuate Dermal Scarring

Abstract: Objective: Demonstrate the impact of IL-10 producing T lymphocytes on mediating dermal scarring. Summary Background Data: We demonstrated that CD4 + cells are essential to improving postinjury wound healing and preventing fibrosis. CD4 + subsets secrete differential cytokine and growth factor profiles, though their role in fibrosis is not known. IL-10, a key anti-inflammatory cytokine shown to promote regenerative wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Similar observations have also been recorded for bone marrow MSC-EVs (BMSC-EVs), which were observed to inhibit T lymphocyte proliferation, boost regulatory T cell numbers, and increase the secretion of anti-inflammatory cytokines such as TGF-β1 and IL-10 [35]. These observations have clear implications in dermal wound healing, since the potent antifibrotic and proregenerative effects of IL-10 have been well described [36,37]. However, wound healing models in which there is an abolition of T cells (athymic mouse models and antibody-mediated depletion) have frequently provided variable results, with examples of regulatory CD4 + and cytotoxic CD8 + T cell neutralisation or knockout generating unreproducible and often contradictory effects on parameters such as collagen deposition or wound breaking strength [38,39].…”
Section: Applications In Regenerative Dermatologysupporting
confidence: 63%
“…Similar observations have also been recorded for bone marrow MSC-EVs (BMSC-EVs), which were observed to inhibit T lymphocyte proliferation, boost regulatory T cell numbers, and increase the secretion of anti-inflammatory cytokines such as TGF-β1 and IL-10 [35]. These observations have clear implications in dermal wound healing, since the potent antifibrotic and proregenerative effects of IL-10 have been well described [36,37]. However, wound healing models in which there is an abolition of T cells (athymic mouse models and antibody-mediated depletion) have frequently provided variable results, with examples of regulatory CD4 + and cytotoxic CD8 + T cell neutralisation or knockout generating unreproducible and often contradictory effects on parameters such as collagen deposition or wound breaking strength [38,39].…”
Section: Applications In Regenerative Dermatologysupporting
confidence: 63%
“…Bollyky et al ( 130 ) demonstrated that HMW-HA promoted the induction of Tr1 cells from effector memory T-cell precursors via binding its receptor, CD44, in humans and mice. The produced IL-10 from Tr1 cells also enforces HMW-HA production from fibroblast via activating the STAT3-dependent signaling pathway in mice ( 131 , 132 ). Therefore, the crosstalk of Tr1 cells and extracellular matrix such as HMW-HA could be essential for wound healing in inflamed tissues.…”
Section: Induction Mechanisms Of Tr1 Cells In Aitmentioning
confidence: 96%
“…For example, IL-10producing CD4+ T lymphocyte subsets, specifically Th1, regulate inflammatory cell cytokine expression to selectively attenuate dermal wound fibrosis. 149 While the NKG2A/CD94 complex (an inhibitory marker of the T cells) was specifically upregulated, it was demonstrated that the downregulation of cytotoxic CD8+ T cells is a keloid signature in peripheral blood and keloid lesions. 150 This may explain the significant decrease in CTLs within the scar tissue boundary.…”
Section: Msc-exo Regulates T-cell Differentiationmentioning
confidence: 99%